Pendidikan Karakterpada Anak Usia Dini: Sudut Pandang Psikologi Perkembangan Anak - Fatmawati Fatmawati (Jurnal Al-Amin: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Developmental psychologists assume that the changes that occur are assumed to achieve something better and produce behaviors that are adaptive, more organized, more effective, and more complex. From various literature studies, physical development is related to changes in bodily functions, intellectual development includes cognitive development and language related to the thinking process. Meanwhile, emotional development refers to developments related to basic human emotions that are felt and expressed, while socio-moral development is related to various changes in children's ways when dealing with the social environment and the various rules and manners that exist. From the above explanation, the authors propose formulation of the following problems: a) What are the important issues in developing children? b) What is the role of education in shaping children's character? c) Who are the sources of children's character formation?Character is a container of various psychological characteristics that guide children to be able to adapt to the variations in the environment they are facing. In other words, the character will "lead" themselves to do something right and not do something that is not right. This character determines whether the child is able or not to adapt to the diversity of situations he faces. This can be seen in the way children behave, which is an accumulation of various good aspects of self formation.Education that stimulates the development of children's character in essence contains studies relating to norms and values ​​that lead to moral formation. It is further explained that every child-oriented parenting and educational activity should contain learning activities that not only involve cognitive aspects, but also involve affective, social and moral aspects. With regard to the formation of children's character, there are five questions that are questioned as a basis for evaluating the educational process that children receive, namely: 1) How does the environment treat children? 2) How does the immediate environment (parents and educators) treat other people when the child is in that situation? children and their environment, both in the family and at school? 4) Are children given the opportunity to practice good character ?, and 5) Is there collaboration between parents and school authorities?Then the sources of character building for children are: 1) family, 2) preschool institutions (educators), 3) peers, 4) religious organizations, and 5) community. Basically, the essence of character education is guiding individuals to form adaptive behavior.